Human Trabecular Meshwork Cells Exhibit Several Characteristics of, but Are Distinct from, Adipose-Derived Mesenchymal Stem Cells - Morgan, Joshua T. (Mary Ann Liebert, Inc., 2014)
Purpose: To support the growing promise of regenerative medicine in glaucoma, we characterized the similarities and differences between human trabecular meshwork (HTM) cells and human mesenchymal stem cells (hMSCs). Methods: HTM cells and hMSCs were phenotypically characterized by flow cytometry. Using quantitative polymerase chain reaction, the expression of myoc, angptl7, sox2, pou5f1, and notch1 was determined in both cell types with and without dexamethasone (Dex). Immunosuppressive behavior of HTM cells and hMSCs was determined using T cells activated with phytohemagglutinin. T-cell proliferation was determined using BrdU incorporation and flow cytometry. Multipotency of HTM cells and hMSCs was determined using adipogenic and osteogenic differentiation media as well as aqueous humor (AH). Alpha-smooth muscle actin (αSMA) expression was determined in HTM cells, hMSCs, and HTM tissue. Results: Phenotypically, HTM and hMSCs expressed CD73, CD90, CD105, and CD146 but not CD31, CD34, and CD45 and similar sox2, pou5f1, and notch1 expression. Both cell types suppressed T-cell proliferation. However, HTM cells, but not hMSCs, upregulated myoc and angptl7 in response to Dex. Additionally, HTM cells did not differentiate into adipocytes or osteocytes. Culture of hMSCs in 20%, but not 100%, AH potently induced alkaline phosphatase activity. HTM cells in culture possessed uniformly strong expression of αSMA, which contrasted with the limited expression in hMSCs and spatially discrete expression in HTM tissue. Conclusions: HTM cells possess a number of important similarities with hMSCs but lack multipotency, one of the defining characteristics of stem cells. Further work is needed to explore the molecular mechanisms and functional implications underlying the phenotypic similarities.